Optimization of Fermentation Medium for the Production of Recombinant Human Antithrombin III from Saccharomyces cerevisiae through Statistical Experimental Designs - Maheswara Reddy Mallu, Sandeep Vemula, Srinivasa Reddy Ronda (Journal of Applied Pharmaceutical Science, 2015)
This work, for the first time reports the optimization of recombinant human antithrombin (rhAT) production in Saccharomyces cerevisiae BY4741 using statistical experimental designs. Most applications of design of experiments (DoE) have concerned optimization of the composition of growth and production culture media. The typical objective is to identify a best selection and quantitative composition of significant medium supplements. In the present study, Plackett-Burman (PB) design followed by central composite design has been employed to evaluate and optimize the suitable culture medium for rhAT production. Influence of raffinose, glutamic acid and vitamin mixture were screened to be significant variables by PB design. The significant nutritional variables were further optimized using central composite design (CCD) for maximum production of rhAT. Central composite design (CCD) has been selected to explain the interaction effect of the three significant variables such as raffinose, glutamic acid, and vitamin mixture. The multiple regression equation (R2=0.9967) was used to optimize significant impact of medium component values to maximize rhAT formation. The optimized values were found to be 23.09765 g/L, 8.01816 g/L and 77.2056 mg/L for raffinose, glutamic acid and vitamin mixture, respectively. The maximum yield of rhAT of 38.97 µg/mL was obtained experimentally using CCD and was very close to the predicted response of 38.93 µg/mL.
Keywords: Optimization, Placket-Barman design, Central composite design, Antithrombin, Saccharomyces cerevisiae.